Analisis Penyajian Laporan Keuangan Sektor Ukm Berbasis Standar Lembaga Permodalan Perbankan - Susi Handayani (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractLower access to bank because UKM cant make financial statement suitable with bank standards. Therefore this research will descript financial statement of UKM and explain many constraints for UKM to compiling financial statement suitable standard in bank. The result of this research proves that without compiling financial statement, UKM can obtain loan from bank (BRI). This is because the bank had not specifies standard for the financial performance as one of the condition to obtain loan. So there is no relation about UKMs capability in compiling financial statement with access capital of bank.